2019
DOI: 10.1177/0194599819835503
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Treatment of Pain during In‐Office Otolaryngology Procedures: A Systematic Review

Abstract: Objective To qualitatively assess practices of periprocedural pain assessment and control and to evaluate the effectiveness of interventions for pain during in-office procedures reported in the otolaryngology literature through a systematic review. Data Sources PubMed, CINAHL, and Web of Science searches from inception to 2018. Review Methods English-language studies reporting qualitative or quantitative data for periprocedural pain assessment in adult patients undergoing in-office otolaryngology procedures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 100 publications
(329 reference statements)
0
12
0
Order By: Relevance
“…21 GSR, or electrodermal activity, measures the electrical activity conducted through sweat glands in the skin. 22 Electrodermal activity is thought to reflect the activity of the sympathetic nervous system (i.e., physiological arousal). Skin sympathetic nerves are activated in response to stress or other stimuli, increasing the permeability of eccrine sweat glands, resulting in changes in skin conductivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 GSR, or electrodermal activity, measures the electrical activity conducted through sweat glands in the skin. 22 Electrodermal activity is thought to reflect the activity of the sympathetic nervous system (i.e., physiological arousal). Skin sympathetic nerves are activated in response to stress or other stimuli, increasing the permeability of eccrine sweat glands, resulting in changes in skin conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…HR is known to increase when patients experience pain 21 . GSR, or electrodermal activity, measures the electrical activity conducted through sweat glands in the skin 22 . Electrodermal activity is thought to reflect the activity of the sympathetic nervous system (i.e., physiological arousal).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Frank et al 13 found that adequate pain control is the cornerstone of success for in-office procedures in otolaryngology. Accurate pain measurement was also found to improve self-reported patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] The otolaryngology literature is still catching up, with recent publications on pain and tolerance of in office procedures, such as vocal fold injections and laryngeal electromyography. [14][15][16] In certain otolaryngologic surgeries, such as tonsillectomy, pain plays quite a significant role in the postoperative experience. 17 There is, however, a paucity of studies evaluating pain after other otolaryngologic surgeries, such as MDL.…”
mentioning
confidence: 99%
“…Pain has been evaluated more extensively in other specialties, such as dentistry and obstetrics 10–13 . The otolaryngology literature is still catching up, with recent publications on pain and tolerance of in office procedures, such as vocal fold injections and laryngeal electromyography 14–16 . In certain otolaryngologic surgeries, such as tonsillectomy, pain plays quite a significant role in the postoperative experience 17 .…”
mentioning
confidence: 99%